A Computer Technique for Solving Linear Fractional Programming Problems by Using Dinkelbach’s Algorithm (Dhaka University Journal of Science, 2016)
In this paper, we introduce a computer oriented technique for solving linear fractional programming (LFP) problems by converting it into a single linear programming (LP) problem. We have used the idea of Dinkelbach’s algorithm. We use a mathematical programming language (AMPL) to develop computer code. A number of numerical examples are used to demonstrate the technique.Dhaka Univ. J. Sci. 64(2): 121-125, 2016 (July)